RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KARYAWAN - Purba, Leo Jhon Sinar; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2023)
The employee management information system at Nazra Swim School (NSS) was created with the aim of improving the performance and service of employees at Nazra Swim School (NSS). Nazra Swim School has a lot of data, one of which is employee data that needs to be stored and processed. Employee data processing is currently still done manually. To facilitate the processing of employee data, an information system is needed to process employee data so that the resulting information is more accurate, efficient and precise. This employee management information system is done using the waterfall method. This information system design includes document flowcharts, system flowcharts, data flow diagrams, context diagrams, database design, conceptual data model (CDM), physical data model (PDM) and user interface design. The employee management information system is designed using the programming language PHP, Notepad++ and MySQL database. implementation of a web-based employee management information system can help administration and employees in managing employee data automatically.